Resolving Australian analogs for an Eocene Patagonian paleorainforest using leaf size and floristics - Merkhofer, Lisa; Wilf, Peter; Haas, M. Tyler; Kooyman, Robert M.; Sack, Lawren; Scoffoni, Christine; Cúneo, Néstor Rubén (American Journal of Botany)
• Premise of the study: The diverse early Eocene flora from Laguna del Hunco (LH) in Patagonia, Argentina has many nearest living relatives (NLRs) in Australasia but few in South America, indicating the differential survival of an ancient, trans‐Antarctic rainforest biome. To better understand this significant biogeographic pattern, we used detailed comparisons of leaf size and floristics to quantify the legacy of LH across a large network of Australian rainforest‐plot assemblages. • Methods: We applied vein scaling, a new method for estimating the original areas of fragmented leaves. We then compared leaf size and floristics at LH with living Australian assemblages and tabulated the climates of those where NLRs occur, along with additional data on climatic ranges of “ex‐Australian” NLRs that survive outside of Australia. • Key results: Vein scaling estimated areas as accurately as leaf‐size classes. Applying vein scaling to fossil fragments increased the grand mean area of LH by 450 mm2, recovering more originally large leaves. The paleoflora has a majority of microphyll leaves, comparable to leaf litter in subtropical Australian forests, which also have the greatest floristic similarity to LH. Tropical Australian assemblages also share many taxa with LH, and ex‐Australian NLRs mostly inhabit cool, wet montane habitats no longer present in Australia. • Conclusions: Vein scaling is valuable for improving the resolution of fossil leaf‐size distributions by including fragmented specimens. The legacy of LH is evident not only in subtropical and tropical Australia but also in tropical montane Australasia and Southeast Asia, reflecting the disparate histories of surviving Gondwanan lineages. Fil: Merkhofer, Lisa. State University of Pennsylvania; Estados Unidos Fil: Wilf, Peter. State University of Pennsylvania; Estados Unidos Fil: Haas, M. Tyler. State University of Pennsylvania; Estados Unidos Fil: Kooyman, Robert M. Macquarie University; Australia Fil: Sack, Lawren. University of California at Los ...